Detection of interaction between ornidazole and albumin by using thermodynamic parameters - MaltaÅŸ Ã‡aÄŸÄ±l, Esra (International Journal of Advanced Chemistry, 2021)
The binding of 1-chloro-3-(2-methyl-5-nitro-1H-imidazole-1-yl) propan-2-ol (Ornidazole) to human serum albumin (HSA) was studied by fluorescence and UV-visible spectroscopy. Interaction of ornidazole (OR) with HSA was identified by Stern-Volmer and Vanâ€™t Hoff equations. The binding constant, Kb and the thermodynamic parameters, âˆ†H, âˆ†S, and âˆ†G at different temperatures were calculated by several equations. Data shows that the fluorescence quenching mechanism of HSA with ornidazole may occur via static quenching. The thermodynamic parameters showed that van der Waals interactions and hydrogen bonds are the major forces for the interaction of ornidazole with HSA. The spectral changes of synchronous fluorescence suggested that both the microenvironment of OR and the conformation of HSA concerning their concentrations have changed during binding.Â Â Â